High-flow nasal cannula for pre- and apneic oxygenation during rapid sequence induction intubation in emergency surgery: A systematic review and meta-analysis - Hong Tang; Yanyan Yang; Hong Li (PLoS ONE, 2025)
Background Rapid sequence induction intubation (RSII) is commonly used in emergency surgeries for patients at high risk of aspiration. However, these patients are more susceptible to hypoxemia during the RSII process. High-flow nasal cannula (HFNC) oxygen therapy has emerged as a potential alternative to traditional face mask (FM) ventilation pre- and apneic oxygenation. This meta-analysis aimed to evaluate the efficacy of HFNC compared to FM during RSII in emergency surgeries. Methods We conducted a comprehensive literature search across PubMed-MEDLINE, EMBASE-OVID, Scopus, and Web of Science databases up to July 20, 2024. Randomized controlled trials comparing HFNC with FM during RSII for emergency surgery patients were included. The primary outcomes were post-intubation arterial partial pressures of oxygen (PaO2) and carbon dioxide (PaCO2). Secondary outcomes included post-intubation end-tidal carbon dioxide concentration (EtCO2), incidence of desaturation, apnea time, lowest peripheral oxygen saturation (Lowest SpO2), and occurrence of regurgitant aspiration. We used the GRADE approach to assess the certainty of evidence and the Cochrane Risk of Bias 2 (RoB 2) tool to evaluate risk of bias. Findings This meta-analysis encompassed six studies, involving a total of 703 patients. HFNC oxygen therapy demonstrated a significant increase in post-intubation arterial PaO2 compared to FM (mean difference = 63.02 mmHg, 95% CI: 8.99 to 117.05, p = 0.02), while no significant difference was observed in arterial PaCO2. Moreover, HFNC substantially prolonged apnea time (mean difference = 19.25 seconds, 95% CI: 1.69 to 36.82, p = 0.03). No statistically significant differences were found between HFNC and FM regarding EtCO2, incidence of desaturation, Lowest SpO2, or regurgitant aspiration. Conclusion This systematic review and meta-analysis indicates that HFNC may be superior to FM for pre-oxygenation and apneic oxygenation during RSII in emergency surgeries, particularly in improving oxygenation. While these findings are promising, further high-quality research is necessary to establish definitive guidelines for HFNC use in this context.